Wise and foolish virgins white women at work in the feminized world of primary school teaching - Galman, Sally Campbell (Lexington Books, 2012)
"Wise and Foolish Virgins: White Women at Work in the Feminized World of Primary School Teaching by Sally Campbell Galman asks the question, what does it mean for an entire profession to be numerically dominated by white women, and what is the relationship between teacher preparation and professional feminization? Galman provides a sharp, unflinching look at the landscape of a profession on the verge of transformation and offers a frank assessment of where teacher education must go in order to maintain its relevance in the new economy. "--